Mandibulectomy for treatment of fractures associated with severe periodontal disease - Carvalho, Carina Marchiori [UNESP]; Rahal, Sheila Canevese [UNESP]; Dos Reis Mesquita, Luciane [UNESP]; Castilho, Maira Sales [UNESP]; Kano, Washington Takashi [UNESP]; Mamprim, Maria Jaqueline [UNESP] (My University, 2015)
Six cases of mandibular fractures associated with severe periodontal disease that had been treated by mandibulectomy, due to intense bone loss, were evaluated retrospectively. The dogs were mainly older, small breed dogs that had suffered a traumatic event. Four dogs had a bilateral mandibulectomy and 2 a unilateral mandibulectomy.